Answer:
(f-g)(x) = x^4 - x^3 - 4x^2 - 3
Step-by-step explanation:
(f-g)(x) = x^4 - x^2 + 9 - (x^3 + 3x^2 + 12)
(f-g)(x) = x^4 - x^2 + 9 - x^3 - 3x^2 - 12
(f-g)(x) = x^4 - x^3 - 4x^2 - 3
Would it be 2:1? I really don't know, I haven't learned that yet, sorry
Answer:
14/15
Step-by-step explanation:
Answer:
x = 8
Step-by-step explanation:
complementary angles sum to 90°
sum the 2 angles and equate to 90
5x + 50 = 90 ( subtract 50 from both sides )
5x = 40 ( divide both sides by 5 )
x = 8
Answer:
20 degrees
Step-by-step explanation:
every triangle had 3 angles that all add up to 180
the problem gives you two angles which are 120+40 which is 160
180-160 is 20 degrees which is whi it is the answer